Impact of L4/5 Posterior Interbody Fusion With or Without Decompression on Spinopelvic Alignment and Health-related Quality-of-Life Outcomes. Issue 10 (December 2020) - Lugue, Marvin Karlo T.; Watanabe, Kei; Yamazaki, Akiyoshi; Izumi, Tomohiro; Tashi, Hideki; Wakasugi, Masashi; Katsumi, Keiichi; Ohashi, Masayuki; Endo, Naoto
Abstract : Study Design: This was a retrospective case control study. Objective: The objective was to determine the impact of single-level interbody fusion at L4/5 with or without concomitant decompression on various spinopelvic parameters and health-related quality-of-life (HRQOL) outcomes. Summary of Background Data: Recently, focus has swayed from a regional concern to a global sagittal alignment, more comprehensive approach in multilevel, corrective fusion for adult spinal deformity. However, only a few comprehensive studies have investigated the relationships between the various related spinopelvic parameters and HRQOL outcomes using single-level interbody fusion. Materials and Methods: In total, 119 patients with lumbar degenerative disorders (mean age, 68 y; 38 males and 81 females) who underwent L4/5 single-level posterior interbody fusion with a minimum 2-year follow-up were included. Participants were divided into 2 groups according to preoperative sagittal modifiers of the SRS-Schwab adult spinal deformity classification. The correlation between spinopelvic parameters and HRQOL outcomes was investigated. Negative or positive values indicated lordosis. HRQOL outcomes were assessed using visual analog scale scores, Japanese Orthopedic Association Back Pain Evaluation Questionnaires (JOABPEQ), and short form-36 (SF-36). Results: L4/5 local lordosis increased from 6.4±4.4 degrees preoperatively to 11.3±4.5 degrees at 2 years postoperatively ( P <0.0001). Further analysis of the results also showed a correlation between change in L4/5 local lordosis and change in lumbar lordosis (LL) ( r s =0.229, P =0.0143). The high pelvic incidence-LL (≥20 degrees, n=28) and high sagittal vertical axis groups (≥5 cm, n=29) had lower scores in walking ability, social life domains of JOABPEQ, and physical component summary scores of SF-36 preoperatively, and 2 years postoperatively. Fusion status did not affect the HRQOL outcomes, except that concomitant decompression at the adjacent disk level yielded lower SF-36 physical component summary scores 2 years postoperatively. Conclusions: Improvement in L4/5 local lordosis possibly triggers a simultaneous sequence of change in total LL after posterior single-level fusion. HRQOL outcomes were negatively affected by both preoperative and postoperative pelvic incidence-LL mismatch and global sagittal malalignment. Level of Evidence: Level III. Abstract : Supplemental Digital Content is available in the text.